Redefining Existing Concrete Compressive Strength Acceptance Standard in Iran Concrete Code (ABA), by Experimental Data - Iman Mohammadi Bidsardareh; Mohammad Mohammadi (Civil Engineering Journal, 2018)
In Iran Concrete Code (ABA), the criteria for calculation of standard deviation (s) are comprehensive and holistic. However, if it would be determined separately for each geographical area, significant changes could occur due to the use of concrete as one of the common materials. This paper analyses the criteria and redefines the acceptance standards for concrete compressive strength in ABA using experimental data available in Kohgiluyeh and Boyer-Ahmad and Fars provinces. The main hypothesis of the study is that using the statistical analysis of the test specimens for three categories C21, C30 and C35 in various projects located in Kohgiluyeh and Boyer-Ahmad and Fars provinces, extracting standard deviations, mean and the compressive strength of the specimens and their comparison with ABA proposed relationships and values, it is possible to propose new amendments for these areas in line with economic savings in national and international projects. In this study using the quantitative Strategy, library - Internet studies, field studies and in cooperation with the concrete labs, required information for 4878 concrete specimens was collected from the above-mentioned areas. By analysing the acceptance regulations for the specimens based on ABA and comparing the standard deviation of these data with the formulas of the regulations, significant results were obtained for the standard deviation factor correction and finally some formulas were suggested for the acceptance of the concrete specimens.